Information visualization: between aesthetic impact and effective communication - Pérez-Montoro, Mario (Anuario ThinkEPI, 2015)
Nowadays, visualization is used in all contexts. However, there is a gap or mismatch between the intensive use of visualization and our low level of visual knowledge. The creation and proper use of effective information visualizations is constrained by rules or principles that guarantee their effectiveness in communicating a message. Many of these principles come from psychology and, specifically, from the theory of perception. Other principles emerge from the structure of information and the visual power of tables and graphs. Despite all of these considerations, two key principles must be kept in mind when creating and using information visualizations within a communications strategy: the principle of objectivity and the principle of data-ink ratio.